The Correlation between Microsatellite Instability and the Features of Sporadic Colorectal Cancer in Sample of Iraqi Patients - Mohymen, Nidal Abdul; Hanon, Basim Mohammed; Mahommod, Akeel Shaker (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Background: Microsatillite instability (MSI) is a mutational signature found in colorectal carcinoma (CRC), it represents about 12% in non inherited CRC. Aim: To correlate between MSI and sporadic CRC Iraqi patients. Patients and methods: A total of 47 patients with colorectal carcinoma were enrolled in this study, among these patients 26 (55%) males and 21(45%) females, with a range age from 37 years to 72 years, mean age (54.5 year). Microsatellite marker amplifications were performed as singleplex PCR reactions. Results: Patients were divided in to three groups, group 1 with MSI high were constituted a frequency of 17 (36.17 %), and group 2 with MSS (16) (34.04%) and group 3 with MSI low the frequency(14 ) (29.78 %). MSI high was expressed in high percentage (38.09%) in women comparted with male( 34.61%),while its relation to age, results indicated that age group (>-50 years) showed high. Percentage (37.93%) compated with Group 1(>-50 years) (33.33% ) and the realtion of MSI with morphological feature of the specimens showed that poorly diffrrentiated CRC specimens showed the highly percentage ( 47.07% ) when comparted with well and moderatly differntiated cases. The mucinous type of CRC reveled 100% pecentage for MSI comparted with nonmucinous ( 27.65%) with siganficant difference. High frequancy of MSI was shown in right site (52.94%) with significant difference compared with MSI L and MSS. Conclusion: This study showed that there were a close association between MSI with female patients, old patients, and right site, mucinous and poorly differentiated CRC.